Közgazdasági kutatások szerepe az oktatási rendszerek fejlesztésében - Károly Fazekas (Hungarian Academy of Sciences, Institute of Economics, 2011)
– The starting point of this paper is a widely shared fundamental preference according to which Hungary should follow a fast, sustainable development path and catch up with the developed world in the foreseeable future. Questions raised in this paper are related to the instrumental preferences. How is catching up most likely to succeed? What is the role of improved education in accelerating economic growth? Once we found the right education policy to align with that goal how can we make the best use of our resources? In what fields economic research can contribute to the betterment of education policy?
Keywords: A12; I21; I28; J24; 330; economics of education; education policy; Bildungsökonomik; Bildungspolitik; Ungarn